Estudo sobre a influência do conforto térmico na capacidade de concentração de trabalhadores da indústria metal mecânica - Belloni, Elias José (Universidade do Vale do Rio dos Sinos, 2014)
Throughout evolution humans sought technique to improve the thermal conditions of their environment , low temperatures were the worst thermal conditions , than with the mastery of fire has become the main instrument used to heat the room on cold days , improving thermal comfort . With the development of civilizations and industry consolidation , during the industrial revolution , jobs to come to be able to heat stress, high and low temperatures , because the concern was with the production without worrying about working conditions and welfare of workers. With the development of industry , the emergence of various standards concern for the welfare and safety of the workers came into force within the industry. This work is to evaluate the ability of concentration of industrial workers during their activities considering the ambient
Keywords: Carga térmica; Conforto térmico; Trabalho; Concentração; Thermal load; Thermal comfort; Work; Concentration